Banker to the poor micro-lending and the battle against world poverty - Yunus, Muhammad 1940-; Jolis, Alan. (New York PublicAffairs, 2007)
The founder of the Grameen Bank relates how he developed the system of micro-credit to help eradicate poverty in countries such as Bangladesh by providing financial education and small loans to rural families.
Introduction -- Number 20 Boxirbat Road, Chittagong -- Bengali in America -- Back in Chittangong -- Stool makers of Jobra Village -- Pilot project is born -- Expanding beyond Jobra into Tangail -- Bank for the poor is born -- Growth and challenges for the bank for the poor, 1984-1990 -- Applications in other poor countries -- Applications in the United States and other wealthy countries -- Grameen in the nineties -- Beyond micro-credit : a new world of Grameen enterprises -- Grameen Bank II -- Future.
Originally published: J.C. Lattes, 1997.
2006 Nobel Peace Prize: Muhammad Yunus and Grameen Bank.
Keywords: Yunus, Muhammad -- 1940-.; Grameen Bank -- History; Bankers -- Bangladesh -- Biography; Social reformers -- Bangladesh -- Biography; Microfinance -- Bangladesh -- History; Rural poor -- Bangladesh -- History